The role of perennial grasses in creating a sustainable feed base by conveyor use - E. N. Pavlyuchik; A. D. Kapsamun,; N. N. Ivanova; V. A. Tyulin; O. S. Silina (Аграрная наука Евро-Северо-Востока, 2019)
Currently, the most urgent task in improving the industry of feed production is the creation of green and raw materials conveyors, which will allow an uninterrupted supply of vegetable raw materials from early spring to late autumn for feeding farm animals and preparing high-quality feed. The research has shown that the most optimal time for mowing alfalfaclover-cereals mixtures with high fodder values is the budding phase - the start of flowering of legume grasses in the conveyor system with 10.6-15.2% of raw protein content in the crop. It was noted that the cultivation of meadow clover varieties of various ripening time mixed with a wide range of alfalfa and cereal grasses lead to the decrease in the effect of unfavorable weather conditions and to 15-20% increase in grass mixtures productivity. The article presents recommendations for the extension of the productive longevity of grass stands up to five years using mixtures with different ripening varieties of meadow clover and alfalfa with grass components of a new generation with productivity up to 32.8 t / ha of green mass.  According to the field test of 2013-2017, the article provides data on the green mass productivity of alfalfa-clover-cereals grass stands with the addition of early ripening varieties of grasses, which for two mowings averaged 29.4 t / ha in 2013-2014 and 30.1 t / ha in 2015-2017.  The methods of creating and using grass mixtures have been indicated, the best time for mowing has been defined by conveyor use of them in the Upper Volga region. The scheme of the green and raw materials conveyor with the use of differently ripening grass mixtures, consisting of new species and varieties of forage grasses of different periods of ripening, is given. It has been established that the use of legume-grass mixtures allows to obtain high-quality raw material for the production of bulk feed within 110-120 days, which acts as the way to increase the efficiency of fodder production. An expanded range of fodder grasses creates the conditions for improving the sustainability of fodder production in less dependence on extreme weather conditions.